The influence of vigisox on clinical, hematological and biochemical indices of cattle - I. A. Arkhipov; A. I. Varlamova; N. V. Danilevskaja (Российский паразитологический журнал, 2016)
In experiments on 20 cattle is studied the influence of vigisox at therapeutic (50 mg/kg), 3 male (150 mg/kg) and 5 male (250 mg/kg) increased doses on clinical, hematological and biochemical indices. Vigisox didn’t negative influence on the body of cattle. Chemotherapeutical index of vigisox is 5. The preparation is safe mean for therapy of the main helminthosis of cattle.